Treating Hypotension in Preterm Neonates With Vasoactive Medications - Joynt, Chloe; Cheung, Po-Yin (Frontiers in Pediatrics, 2018)
Preterm neonates often have hypotension which may be due to various etiologies. While it is controversial to define hypotension in preterm neonates, various vasoactive medications are commonly used to provide the cardiovascular support to improve the blood pressure, cardiac output or to treat shock. However, the literature on the systemic and regional hemodynamic effects of these antihypotensive medications in neonates is deficient and incomplete, and cautious translation of findings from other clinical populations and animal studies is required. Based on a literature search on published reports, meta-analytic reviews and selected abstracts, this review discusses the current available information on pharmacologic actions, clinical effects and side effects of commonly used antihypotensive medications including dopamine, dobutamine, epinephrine, norepinephrine, vasopressin and milrinone in preterm neonates.